Little miss stoneybrook and dawn - Martin, Ann M. (New York : Scholastic, 1989)
Each member of the Baby-sitters Club sponsors a different girl in the Little Miss Stoneybrook competition, as Dawn also tries to cope with the break-up of her family after her parents are divorced.
"An Apple paperback."
Keywords: Beauty contests -- Juvenile fiction; Family life -- Juvenile fiction; Babysitters -- Juvenile fiction